Atypical Brain Structures as a Function of Gray Matter Volume (GMV) and Gray Matter Density (GMD) in Young Adults Relating to Autism Spectrum Traits - Yaxu, Yu; Ren, Zhiting; Ward, Jamie; Jiang, Qiu (Frontiers in Psychology, 2020)
Individuals with autistic traits are those who present in the normal population with characteristics of social, communication, personality, and cognitive impairments but do not meet the clinical threshold for autism spectrum disorder (ASD). Most studies have focused on the abnormalities in ASD patients rather than on individuals with autistic traits. In this study, we focused on the behaviors of a large sample (N=401) of Chinese individuals with different levels of autistic traits, measured using the Autism Spectrum Quotient (AQ), and applied voxel-based morphometry (VBM) to determine their association to differences in brain structure. The results mainly showed that the correlation between gray matter volume (GMV) and gray matter density (GMD) of the brain and the AQ was significant in these regions: the left orbitofrontal cortex (OFC), right middle frontal gyrus (MFG), which are involved in social processing and social reasoning; the bilateral parahippocampal gyrus (PHG), which is involved in socioemotional behaviors and unconscious relational memory encoding; and the right superior parietal lobule (SPL), which are involved in cognitive control and the ability to show attention to detail. These findings reveal that people with autistic traits in the normal population have atypical development in GMV and GMD, which may affect their social functioning and communication ability.